Association of meeting the 24-hour movement guidelines with heart rate variability in adults - De Moraes-Ferrari, G (SPRINGER, 2026)
Objective To analyze the association between 24-hour movement guidelines and heart rate variability (HRV) in adults. Methods The sample consisted of 221 participants (41 +/- 16 years). Cardiac autonomic modulation was assessed through HRV. Physical activity (PA) and sedentary behavior (SB) were assessed using the Actigraph GT3X accelerometer, and sleep was assessed through self-report. The 24-hour guidelines were assessed by aggregating moderate/vigorous PA (>= 150 min/week), sleep (7 to 9 h per day), and SB (<= 8 h). The association between HRV and the guidelines was demonstrated by the General Linear Model method, considering Poisson regression adjusted for sex, age, and socioeconomic status. Statistical significance was calculated at p-value < 0.05 and 95% confidence interval (CI). Results When considering the isolated components, only physical activity was related to higher RMSSD (beta = 0.62, 95%CI = 1.07;7.15), SDNN (beta = 0.26, 95%CI = 0.05;0.47), SD1 (beta = 0.63, 95%CI = 0.17;1.07), and SD2 (beta = 0.22, 95%CI = 0.02;0.42). Meeting two or three components of the 24-hour guidelines was also associated with greater parasympathetic [RMSSD (two: beta = 0.50, 95%CI = 0.07;0.93, three: beta = 0.64, 95%CI = 0.15;1.09), SD1 (two: beta = 0.54, 95%CI = 0.10;0.98, three: beta = 0.65, 95%CI = 0.20;1.10)] and global modulation [SDNN (two: beta = 0.24, 95%CI = 0.06;0.43, three: beta = 0.38, 95%CI = 0.15;0,61), SD2 (two: beta = 0.20, 95%CI = 0.02;0.37, three: beta = 0.35, 95%CI = 0.12;0.58)]. Conclusion Meeting a greater number of components of the 24-hour guidelines was related to greater HRV.
Keywords: Cardiovascular system; Sedentary behavior; Physical activity; Health